Il ruolo del confronto nella critica artistica (Itinera, 2013)
The topic of this paper is comparison and classification among artworks. In the first section, I underline the importance of comparison in art criticism, as acknowledged by contemporary philosophers such as Sibley, Vaida and D’Angelo. In the second section, I analyze the nature of comparison as treated by Eighteen century British empiricists such as Hume and Gerard, who recognized, implicitly or explicitly, the existence of two levels of comparison, one involving sensibility and the other relying on reasoning and leading to classification among artworks and species of beauty. In the third and last chapter, I return to the recent analytical debate (Pratt, Vermazen, Dickie and Carroll) and establish both the limits of classification and the real point of comparison, which amounts to refine our taste and achieve a deeper understanding of artworks.